Feeding more people and better in West Africa: the case of Benin - Mensah, Moïse C. (International Food Policy Research Institute, 1999)
In this lecture, Moïse C. Mensah traces the recent history of economic policy in Benin and examines how Benin can meet food security needs while overcoming the challenges posed by a growing population, fragile natural resource base, and constraints on productivity. Although the gap between food supply and demand is not significant in Benin, about a third of the population is food insecure because of regional differences in food production and lack of income. The growth in population means that Benin’s food requirements will double in volume by 2020, possibly increasing the food-insecure share of the population. To help make the Beninese food secure, Mensah suggests that several steps be taken in three areas: agricultural and rural development, agricultural research, and regional cooperation. These steps include faster decentralization of government in order to empower local communities, improvement of infrastructure and rural services, enhancement of market efficiency, promotion of income generation in rural areas, improvement in the link between farmers’ needs and research themes and extension packages, strengthening of the capability for food policy analysis and research, and better integration of Benin into regional marketing and cooperation. (Forward by Per Pinstrup- Andersen)